Productivity of integrated harvesting of pulpwood and energy wood in first commercial thinnings - Andersson, Robert (2011)
The aim of this study was to quantify the productivity and the costs of different harvesting systems (teams), containing harvesters equipped with accumulating harvester heads and forwarders, in first commercial thinnings were an integrated harvest of pulpwood and energy wood were performed. In the beginning the plan was to study and measure 20 sites before and after harvest. Due to storms during the summer of 2010, complete data could only be obtained from 8 of these 20 sites. Seven of these sites were privately owned and one was owned by UPM, all of the sites had been pre-commercially thinned. The mean stem density before harvest was 2578 stems per ha and the mean stem volume was 0.074 m3solid over bark.